The photo response properties of shape memory alloy thin film based photodiode - Canbay, C. Aksu; Karaduman, Oktay (Elsevier, 2021)
In this work, the CuAlMn shape memory alloy (SMA) composed as Cu-12.28Al-2.84Mn in wt.% (= 72.49Cu-24.70Al-2.81Mn in at.%) was used as a thin Schottky contact layer on an n-Si wafer to produce a Schottky type Al/CuAlMn/n-Si/Al photodiode. To do this, in the first stage of the experimental route, the CuAlMn alloy was prepared in succession by casting in arc melter, homogenizing in beta-phase region and lastly by quenching in iced-brine water. Then, the shape memory effect characteristics were revealed by the widely-used thermal (DSC and DTA) and structural (EDS and XRD) characterization tests that been carried out on the alloy. Then, the alloy was thermally evaporated and deposited on the n-Si wafer as a thin film nano layer to make the Al/CuAlMn/n-Si/Al photodiode. The current-voltage (I-V) analysis of the diode taken under dark and different light intensities revealed the rectifying behavior of the diode. The work function value of CuAlMn alloy film was determined as 4.747 +/- 0.17 eV. The reverse bias current values the diode under light were found to be greater than the value observed under dark. The results showed that the diode has a considerable photoconducting feature. The characteristic electrical diode parame-ters of the junction were computed by using the traditional I-V method. By taking into consideration the literature works related to SMA layered photodiodes, some of the photodiode parameters such as responsivity, photosensitivity, and detectivity, not been reported so far, were determined for the first time. The SMA/n-Si device showed an excellent photosensitivity (similar to 10(5)) performance, and also good merits of responsivity, and detectivity. Which implied that the produced device can be used in various optoelectronic applications. The transient photocurrent (TPC) measurement was performed under the various light intensity conditions and the related characteristic photodiode parameters were determined. Additionally, the capacitance-voltage (C-V) measurement of the SMA-layered photodiode was also carried out at room temperature and different frequencies. The capacitance of the device was observed to be quite sensitive to frequency. Furthermore, a solution suggestion for SMA film cracks and related fractures was also discussed. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Thin film SMA layered Schottky photodiode; Photosensitivity; Responsivity; Current-voltage